Variability of the hearing threshold tracings in automatic audiometry beyond the initial transient phase - JAROSZEWSKI, Antoni; RAKOWSKI, Andrzej (Archives of Acoustics, 1977)
The results of measurements and the analysis of variability of the hearing threshold observed in automatic audiometry beyond the initial transient phase are given. The methods of interpretation of the threshold tracings and their adequacy with respect to various rates of the test signal level control are discussed.